Lipid Profile of Larix cajanderi Mayr in Adaptation to Natural Conditions in the Cryolithozone - Vasiliy V. Nokhsorov; Tatiana D. Tatarinova; Lyubov V. Dudareva; Natalia V. Semenova; Trofim C. Maximov (International Journal of Molecular Sciences, 2024)
The prevalence of coniferous trees in the forest landscapes of northeastern Siberia is conditioned by their high frost resistance. The Kajander larch (Larix cajanderi Mayr), which can survive under natural conditions (down to −60 °C) in the cryolithozone of Yakutia, is the dominant forest-forming species. We hypothesise that our study using HPTLC–UV/Vis/FLD, TLC–GC/FID, and GC–MS methods of seasonal features of the lipid profile of Kajander larch tissues will bring us closer to understanding the mechanisms of participation of lipid components in the adaptation of this valuable tree species to the cold climate of the cryolithozone. Rare delta5-unsaturated polymethylene-interrupted fatty acids (∆5-UPIFA) were identified in the fatty acids (FAs) of L. cajanderi shoots, including 18:2(Δ5.9) (taxoleic), 18:3(Δ5.9.12) (pinolenic), and 18:4(Δ5.9.12.15) (coniferonic). It was found that the content of ∆5-UPIFA in L. cajanderi shoots markedly increased (1.5-fold, representing up to 23.9% of sum FAs) during the autumnal transition of trees to dormancy. It was observed that the ranges of low temperatures experienced during the prolonged winter period primarily determined the structural diversity of membrane lipids and their constituent FAs during the cold adaptation of L. cajanderi. The results obtained can be used for the selection of molecular markers of cold tolerance in woody plants, including fruit trees.